The Idea of Nzhdeh on the Synthetic Modernization of the Armenian Identity - Sargsyan, Armen (Bulletin of Yerevan University E: Philosophy, Psychology, 2017)
The problem of the modernization of the Armenian identity, the spiritual renewal of the nation occupies an important place in the creative heritage of Garegin Nzhdeh, which he solves from the position of the synthetic approach. According to the convictions of the Armenian thinker, the modernization of the Armenian identity should be based both on the achievements of modern "weapons", scientific achievements, and on the viable values of the past. Nzhdeh is against national selfisolation and with regard to the issue of modernization of the Armenian identity rejected the state of becoming a "stranger", rather than the foreign values.